Entomogenous fungi from North-East India - L. K. HAZARIKA, K. C. PUZARI and (Indian Phytopathology, 2002)
Field survey in rice ecosystem on rainfed rice recovered 240 cadavers of rice hispa, Dieladispa armigera (Olivier) (Coleoptera, Chrysomelidae). The entomogenous association was formed/established by the fungi on the insects are Beauveria bassiana (Bals.) Vuill., Aspergillus flavus Link., Fusarium heteroporum Nees ex Fr., Penicillium eyelopium Westling, Geotrichum sp. and Mucor sp. The former three were found as entomopathogenic while the remaining two are of opportunistic in association. B. bassiana and A. flavus showed their potentiality as biocontrol agents.